Effect of drought and plant density on radiation interception, radiation use efficiency and patitioning of dry matter to seeds in cowpea - Craufurd, Peter Q.; Wheeler, T.R. (1999)
The effects of drought and plant density on fractional interception (f), radiation-use efficiency (RUE) and dry matter accumulation and partitioning to seeds in cowpea (Vigna unguiculata) need to be quantified in order to calibrate cowpea simulation models for West Africa. Accordingly, a short duration cultivar of cowpea, IT84S-2246-4, was grown at a range of plant densities in well-watered and drought conditions in 1990–91 at two contrasting locations in Nigeria, Ibadan (7°N) and Kano (12°N). Fractional interception of radiation (f) and total above-ground dry matter accumulation (TDM) were measured throughout the growing season and TDM and seed yield (SY) were measured at maturity. At Ibadan drought had no effect on phenology while at Kano drought increased the duration of the vegetative phase (by 5–6 days), but not of the reproductive phase. Drought reduced f and radiation-use efficiency (RUE), and hence TDM, and there were significant interactions between RUE and plant density at both Kano and Ibadan. Average SY in the well-watered treatments at Kano and Ibadan were 1600 and 700 kg ha⊃−1&/sup; respectively and drought reduced SY by 50% at both sites but did not interact with plant density. Across locations, plant densities and drought treatments SY was strongly correlated (r = 0.96) with TDM production between flowering and maturity. These data suggest that partitioning of dry matter during the reproductive phase is not affected by location, drought or plant density and the SY of cowpea can be predicted from dry matter accumulation.